2022
DOI: 10.3390/foods11040558
|View full text |Cite
|
Sign up to set email alerts
|

Turmeric-Fortified Cow and Soya Milk: Golden Milk as a Street Food to Support Consumer Health

Abstract: We studied plant-based milk from soya beans as a means to release and convey the bound antioxidants in turmeric to benefit consumer health. This was compared to cow milk as a carrier because soya milk consumption as an alternative to cow milk is increasing globally. Hence, turmeric paste was added to milk to investigate the release of turmeric antioxidants when changing the matrix (cow vs. soy), the amount of turmeric paste (0%, 2%, and 6%), and the effect of heating (with and without). Proximate, physicochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…The addition of turmeric increased the antioxidant activity due to the presence of curcumin, the main antioxidant compound in turmeric [16]. This results also in accordance with previous research [11,17], where milk with the addition of turmeric has a higher antioxidant activity when compared to milk and the more turmeric is added, the higher the antioxidant activity.…”
Section: Analysis Of Antioxidant Activitysupporting
confidence: 90%
See 1 more Smart Citation
“…The addition of turmeric increased the antioxidant activity due to the presence of curcumin, the main antioxidant compound in turmeric [16]. This results also in accordance with previous research [11,17], where milk with the addition of turmeric has a higher antioxidant activity when compared to milk and the more turmeric is added, the higher the antioxidant activity.…”
Section: Analysis Of Antioxidant Activitysupporting
confidence: 90%
“…Sample were centrifuged at 3000 rpm for 10 min to collect the supernatant. The analyses of antioxidant activities was done based on DPPH radical scavenging method with some modifications [11] using wavelength 517 nm. The following equation was used to calculate antioxidant activities as a percentage of free radical inhibition:…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…Leksawasdi et al (40) fortified green soybean milk with the addition of green soybean pod extract and also reported a significant increase in TPC, while other authors reported similar results with different dairy products fortified with herbal extracts (41). An increase in TPC from 0.01 to 0.15 g/kg along with an increase in antioxidant capacity from 7.5 to 17.7 (mmol/kg) associated with fortification of whole milk and soy drink with turmeric was also observed by Idowu-Adebayo et al (42).…”
Section: Antioxidant Activitysupporting
confidence: 72%
“…Overall, antioxidant activity increased with increased turmeric concentration. Idowu-Adebayo et al [34] observed a similar trend in a turmeric-fortified milk product. Both phenolic and flavonoid compounds in turmeric juice have been found to increase antioxidant activity [27], especially curcumin and demethoxycurcumin [35,36].…”
Section: Total Antioxidant Capacity and Dpph Inhibitionmentioning
confidence: 67%
“…TFP juices with 10% or higher turmeric showed significantly higher DPPH inhibition percentage than juice with 5% turmeric, and there was no significant difference among 10%T, 15%T, and 20%T ( Table 3 ). Similarly, Idowu-Adebayo et al [ 34 ] showed that adding either 2% or 6% turmeric into whole and skimmed milk did not significantly change the total antioxidant capacity.…”
Section: Resultsmentioning
confidence: 97%